Pengaruh Konsumsi Minuman Lokal Terhadap Flour Albus dan Akne Vulgaris Pada Siswi SMA di Kab. Kolaka - Arliatin Arliatin; Rahmiyani Saad; Hartati S (Jurnal Ventilator, 2023)
About 85% teenagers experience akne vulgaris. This study aims to analyze the influence of consuming local beverage to the signs and symptoms of Flour albus and Akne vulgaris to high school students in Kolaka regency. It is an experimental study, quasy experiment method with two groups of pretest and post-test design. Population consist of all women high school student suffering with Flour albus and Akne vulgaris as many as 20 respondents, which divided into 2 groups, they are 10 experiment samples providing local beverages containing 3 mixed fruits (jackfruit, melon, kersen) and 10 control samples. This study is prepared using computerized system with SPSS program. Data analysis assays applied is NPar-test. Study results obtained that there is any influence of consuming local beverage to the decrease of signs and symptoms of Flour albus, which p value = 0.000 (p<0.05), there is a significant influence of consuming local beverages to the signs and symptoms of Flour albus where p value =0.001 (p<0.05) The conclusion of this study is there is an influence of consuming local beverage to the decrease of the signs and symptoms of Flour albus and Akne vulgaris to the women high school students in Kolaka regency.